Biological Actions, Electrical Conductance and Silicon-Containing Microparticles of Arsenicum Album Prepared in Plastic and Glass Vials - Dalboni, Luciane Costa; Coelho, Cideli de Paula; Palombo Pedro, Renata Rossettini; Correia, Michelle Sanchez; de Santana, Fabiana Rodrigues; Cardoso, Thayná Neves; Pinto, Sandra Augusta G.; Alvares-Saraiva, Anuska M.; Dutra-Correa, Maristela; Peres, Giovani B.; Holandino, Carla; Rossi, André; César, Amarilys de Toledo; Waisse, Silvia; Bonamin, Leoni Villano (Homeopathy, 2019)
Introduction According to the “silica hypothesis” formulated to explain homeopathy, the information of starting materials would be transferred to cells by silica nanoparticles detached from the glassware walls by serial dilution and agitation through epitaxy. We compared the biological activity, electrical current and silicon microparticle content (by means of scanning electron microscopy/energy-dispersive X-ray spectroscopy) of high dilutions (HDs) of arsenic prepared in plastic and glass vials to investigate the role of silica in their biological effects in vitro.Materials and Methods Co-cultures of macrophages and yeast (Saccharomyces cerevisiae) were treated with different HDs of arsenic prepared in plastic and glass vials. Macrophage morphology, phagocytosis index, nitric oxide (NO), and cytokine production were evaluated.Results Measurable amounts of silicon microparticles were detected only in the HDs prepared in glass vials, but ultra-centrifugation eliminated them. Specific and non-specific results were observed. Non-specific pro-inflammatory effects were seen in all dilutions prepared in plastic vials, including elevation of pro-inflammatory cytokines, NO and macrophage phagocytic index. Only the 200th centesimal dilution of arsenic produced specific decrease in interleukin-6 production in macrophages, and it was independent of the vial type or the presence of microparticles of silica in the medicine samples. The nature of the vials had an impact on the electric flow in the respective fluids.Conclusion The non-specific, pro-inflammatory effects might be attributed to organic residuals detached from the vials' plastic walls during manipulation. Instead, specific silica-independent effects of the homeopathic medicine can be attributed to the decrease of interleukin-6 after treatment with the 200th centesimal dilution of arsenic.
Keywords: arsenic; macrophages; microparticles; conductance; silicon; homeopathy